Human Resource Competence and Organizational Culture on Employee Performance through Work Discipline - M. Risal; Dharmawan, Yandhi Yudhi; Utary, Anis Rachma (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2024)
The purpose of the study was to measure the influence of human resource competence and organizational culture on employee performance through work discipline, the research was conducted on employees of PT. Arexas Indonesia in Balikpapan City. The analytical tool technique used is SEM-PLS with a sample of 78 employees. The analyss data collection techniques using questionnaires with a Liker scale, the results of data management show that transformational leadership does not have a positive and significant effect on organizational commitment, organizational culture has a positive and significant effect on organizational commitment, transformational leadership has a positive and significant effect on job satisfaction, organizational culture has a positive and significant effect on job satisfaction, organizational commitment Positive and significant effect on job satisfaction.